A survey on the awareness and knowledge about elective oocyte cryopreservation among unmarried women of reproductive age visiting a private fertility center - Yeon Hee Hong; Jeong Woo Park; Hyein Kim; Seul Ki Kim; Chang Woo Choo; Byung Chul Jee; Chang Suk Suh; Seok Hyun Kim (Obstetrics & Gynecology Science, 2019)
ObjectiveThe aim of this study was to investigate the level of awareness and knowledge regarding elective oocyte cryopreservation (OC) among unmarried women of reproductive age in Korea.MethodsA survey was conducted among 86 women who visited a fertility preservation clinic for counseling about elective OC between December 2016 and May 2018. Participants were asked to fill out a questionnaire regarding their awareness and knowledge of fertility and OC.ResultsThe questionnaire was completed by 71 women. Among them, 73% decided to undergo OC after counseling. The main reason for making this decision was that they wished to maintain their fertility in the future (70.6%). Conversely, the high cost for the procedure was the main reason given by those who chose to forego this procedure. Regarding fertility and OC, the participants' knowledge was poor. Most women expected greater financial support from the government or from their place of employment.ConclusionThis study demonstrated that the awareness and knowledge about elective OC were relatively poor among the female Korean population. These findings may help clinicians in better counselling of their patients.